Determinan Pengungkapan Emisi Karbon: Sebuah Studi di Sektor Energi - Desiana Desiana; Ulfa Luthfia Nanda; Iwan Hermansyah (Politeknik Ganesha Medan, 2025)
The issue of global warming is an issue that attracts the world's attention, the increase in carbon emissions released by industry and motor vehicles is suspected to be the cause, the world is committed to reducing the effects of greenhouse gases in the Kyoto Protocol, the Kyoto Protocol is an international convention that agrees to reduce the effects of greenhouse gases implemented in Kyoto in 1997. This study aims to see the effect of environmental performance, financial performance, company size, reputation of public accounting firms and company age on carbon emission disclosure, the population in this study are energy sector companies listed on the Indonesian Stock Exchange for 2018-2022 that publish annual reports and/or sustainability reports, the sampling technique uses purposive sampling, the total sample in this study is 90 energy sector companies that meet the criteria, the analysis technique uses multiple linear regression analysis to test the hypothesis. The results of this study indicate that environmental performance and company age have a significant effect on carbon emission disclosure, while financial performance, reputation of public accounting firms and company size have no effect on carbon emission disclosure